Mesenchymal Stem Cell-Engrafted Bacterial Cellulose and Graphene Oxide Scaffolds Enhance Peripheral Nerve Repair in a Rat Model - Simsek, Ismail; Unal, Semra; Cekic, Efecan; Dogan, Ecem; Kirazli, Ozlem; Harman, Ferhat (WILEY-V C H VERLAG GMBH, 2025)
Peripheral nerve injuries result in significant functional impairment, and limited regenerative capacity within the central nervous system further complicates recovery. This study investigates the effects of graphene oxide-decorated bacterial cellulose (BC/GO) scaffolds, with or without mesenchymal stem cells (MSCs), on axonal regeneration following sciatic nerve injury in rats. Twenty-seven male rats were assigned to autograft, BC/GO, and BC/GO+MSCs. The sciatic functional index (SFI), electromyography (EMG), and histopathological analysis were evaluated at 8 weeks. Although SFI scores showed no significant differences, compound muscle action potential (CMAP) values at 4 weeks were significantly higher in both the BC/GO and BC/GO+MSCs groups compared to autografts. Macroscopic examination revealed extensive tissue adhesions in the BC/GO and BC/GO+MSCs groups. Histological analysis indicated regeneration across all groups. The autograft group showed no inflammation, whereas the BC/GO group demonstrated the highest levels of inflammation and degeneration. The BC/GO+MSCs group exhibited reduced inflammation, likely due to the immunomodulatory effects of MSCs. While BC/GO scaffolds promoted early regeneration, the inflammatory response compromised the long-term outcomes. These findings suggest BC/GO scaffolds can facilitate initial nerve repair but require further refinement to sustain long-term functional recovery.
Keywords: bacterial cellulose; graphene oxide; implantable scaffold; mesenchymal stem cells; peripheral nerve injury; NANOCOMPOSITES; REGENERATION; TISSUE; TOOL; Materials Science; Polymer Science